PENGARUH MODEL PEMBELAJARAN REACT TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 2 PAYAKUMBUH - Fardatil Aini Agusti (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical reasoning skills are one of the goal in mathematics learning that must be achieved by students. But in reality at SMP Negeri 2 Payakumbuh this ability is still not optimal and don’t facilitated yet for improving those skill well. One effort to overcome these problems is to apply the Relating, Experiencing, Applying, Cooperating, Transferring(REACT) model. The aims of this research is to describe the differences in the ability of student's mathematical reasoning using REACT model with the ability of student's mathematical reasoning using conventional learning model. The types of research is quasi-experimental with Randomized Control-Group Only Design. The authentication of the research hypotheses using t-test. Based on the results of data analysis, it was concluded that the mathematical reasoning skills of students who learn using the REACT model is better than the mathematical reasoning skills of students who learn by conventional learning in class VIII SMP Negeri 2 Payakumbuh. Keywords — Mathematical reasoning skills, REACT, Conventional learning